Supporting the learning and networking experiences of doctoral students - Thomson, Chris; Allan, Barbara (Proceedings of the International Conference on Networked Learning, 2010)
This study explores the impact of a Graduate Virtual Research Environment (GVRE) on the learning and networking experiences of research students. The GVRE was established to support and enhance research skills and employability training across a university. It provides an extensive range of resources including video reflections based on the experiences of students and staff; GVRE members are encouraged to comment and engage in discussions on these resources. Our work is framed using social theories of learning and the role of communities in the support and development of research students. In particular, we are interested in exploring the challenges involved in developing communities and networks for students whose main focus is their individual research. The GVRE was made available to over 600 students and in this research we explore its impact on the experiences of research students. In particular, we investigate four questions: (a) what impact does the students use of the GVRE have on the development of their research skills; (b) what impact does membership of the GVRE have on the networks and communities of research students; (c) how do research students view the relationships between their research skills training programme, their individual research and the GVRE; and (d) how do research students currently use social media. We use an interpretivist approach and our data sources include site statistics, responses to a questionnaire and also feedback from a focus group. Our findings indicate that networking remains an issue and students suggested approaches to facilitating this using the GVRE: (1) A clearer pathway from skills need identification to skills acquisition; (2) Rewards for activities around networking - possibly through credit on the training scheme; (3) Activities that would involve research directly. Feedback on the GVRE indicated that it is valued by research students as it facilitates the development of their research skills. In terms of marketing the GVRE to research students important factors identified were: the ease of access to the site, the overview it gives of the PhD process; and the value of the site to students around the defining moments of their studies when the students felt they needed additional advice and guidance.